No increased risk of acute osteomyelitis associated with closed or open long bone shaft fracture - Grigorian, Areg (J Clin Orthop Trauma, 2019)
OBJECTIVES: Osteomyelitis of the long bones can result from hematogenous spread, direct inoculation or from a contiguous focus of infection. The association of osteomyelitis after long bone fractures has widely been believed to be true by practicing surgeons since the 1950s, even though the evidence has been poor. We hypothesized that long bone shaft fracture and major bone surgery are independent risk factors for osteomyelitis in adult trauma patients. METHODS: The National Trauma Data Bank (NTDB) was queried between 2007 and 2015 for patients ≥18 years of age presenting after trauma. Patients with long bone shaft fractures (femur, tibia/fibula, humerus) were identified and rate of acute osteomyelitis was calculated. Univariable logistic regression was performed. A multivariable logistic regression was performed to identify risk factors for development of acute osteomyelitis. RESULTS: From 5,494,609 patients, 358,406 were identified to have long bone shaft fractures (6.5%) with the majority being tibia/fibula (44.3%). The osteomyelitis rate in long bone shaft fractures was 0.05%. Independent risk factors for osteomyelitis included major humerus surgery and major tibia/fibula surgery. The strongest risk factor was non-pseudomonas bacteremia. Long bone shaft fractures were not found to be an independent risk factor for osteomyelitis (p > 0.05). CONCLUSIONS: Long bone shaft fractures are not independently associated with increased risk for osteomyelitis. Major extremity surgery on the humerus and tibia/fibula, but not femur, are independent risk factors for osteomyelitis. However, the strongest risk factor is non-pseudomonas bacteremia.